Unraveling the Complex Dynamics of Islamic Social Reporting and Financial Performance: A Study of Mediating and Moderating Factors in Islamic Banks - Saipul Arni Muhsyaf (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Islamic Social Reporting (ISR) is crucial for Islamic banks as it captures the extent of their adherence to social and ethical principles, which influences their financial performance. Drawing on stakeholder theory the primary objective of this study is to scrutinize the impact of ISR on the financial performance of Islamic banks in Indonesia, with a specific focus on the mediating and moderating roles of key governance factors, namely ownership concentration, bank size, board independence composition, and leverage. The study is based on data from ten Indonesian Islamic commercial banks from 2017 to 2020, utilizing regression models and Path SEM analysis for assessment. The findings reveal a positive impact of ISR on financial performance. Additionally, it is discovered that the board independence composition and leverage significantly moderate the ISR-financial performance relationship. However, the study does not find evidence of the mediating effects of ownership concentration and bank size. While the moderating roles of board independence composition and leverage align with prior research, the absence of mediation effects contrasts with previous studies. Originality/Value: This research offers a distinct exploration of the relationship between ISR-financial and financial performance relationship within the specific context of Indonesian Islamic banks. It creatively probes the mediating and moderating impacts of select governance variables, a largely unexplored territory in extant literature. The findings of this study contribute to the theoretical framework of ISR's influence on financial performance and provide actionable insights for policy and strategic decisions in Islamic banks. It underscores the potential of such studies to drive sustainable growth, thereby laying the groundwork for future research.